Improving Vocabulary Students Through Picture - Laohan, Sri Arista Mita Dewi; Ronny Tuna, Jim; Liando, Nihta V. F (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
ABSTRACT The aim of this research is to find out whether the use of pictures can improve students' vocabulary or not. In this research the writer uses pictures in teaching English vocabulary because pictures can improve students' vocabulary. In conducting this research, the writer used quantitative research methods through pre-experimental design with one group pre-test and post-test. Data is collected through tests. The types of instruments used are multiple choice (optional), matching and true or false which consists of 30 questions. The population of this study were students at SMP Negeri 4 Bunta. The sample was taken from class VII students for the 2023/2024 academic year at SMP Negeri 4 Bunta. Data were analyzed using the average score formula. The results showed that the average pre-test score was 43.47 while the average post-test score was 79.00. It can be calculated that using pictures in teaching English vocabulary can improve students' vocabulary. Keywords: Improving, Vocabulary and Picture, EFL, Junioh High School